2009
DOI: 10.1007/s12032-009-9214-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum bone turnover markers may be involved in the metastatic potential of lung cancer patients

Abstract: The aim of this study was to investigate several bone markers in Non-Small Cell Lung (NSCLC) and Small Cell Lung (SCLC) patients experiencing or not secondary bony disease. Fasting serum levels of bone formation, bone resorption, and osteoclastogenesis markers were determined in 22 NSCLC patients with bone metastases, 18 without bone metastasis, and 28 SCLC patients. A total of 29 healthy volunteers were also included in the study. Decreased osteocalcin (OC) serum levels and increased osteopontin and ligand of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 23 publications
2
27
1
9
Order By: Relevance
“…The present study found that the sRANKL levels were significantly higher in the NSCLC patients compared with the healthy controls or patients with lung benign space-occupying lesions. In accordance with these results, the study by Karapanagiotou et al also demonstrated higher sRANKL levels in NSCLC patients (20). However, there was no difference in the OPG levels among the three groups in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found that the sRANKL levels were significantly higher in the NSCLC patients compared with the healthy controls or patients with lung benign space-occupying lesions. In accordance with these results, the study by Karapanagiotou et al also demonstrated higher sRANKL levels in NSCLC patients (20). However, there was no difference in the OPG levels among the three groups in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no difference in the OPG levels among the three groups in the present study. This finding was not consist with the results in the study by Karapanagiotou et al, where it was concluded that higher OPG levels promoted the development of lung cancer metastasis (20). This may be due to the relatively small sample size resulting in selective bias.…”
Section: Discussioncontrasting
confidence: 85%
“…We also found that in the group with bone metastasis the OC level decreased, whereas the BALP level was significantly higher. Recently Karapanagiotou et al [26] found that OC serum levels, when compared to the healthy control group, were significantly decreased in NSCLC patients with bone metastasis but not in the other groups. Dane et al [18] found no difference in serum OC values in groups with bone metastasis and without bone metastasis, as in our results despite different methods.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism for the development of lung cancer bone metastasis is not fully understood; but insights into how the bone can harbor tumor cells leading to distortion of the normal bone remodeling activities have been useful in identifying some intriguing therapeutic targets. It is generally believed that the bone is a favored metastatic site for many reasons, which include [11, 2224] (i) high blood flow especially to the red marrow coupled with abundant sinusoids, (ii) sluggish blood flow in the metaphysis facilitating intimate interaction between endothelium and tumor cells, (iii) a large source of immobilized growth factors (such as transforming growth factor, insulin-like growth factors, fibroblast growth factors, platelet-derived growth factors, bone morphogenetic proteins, and calcium), and (iv) continuous and dynamic turnover of bone matrix that can unlock vast resources (cytokines and growth factors) that are needed for tumor survival. Many investigators have represented the pathogenesis of bone metastasis as a vicious cycle that is based on the crosstalk between tumor cells and bone microenvironment leading to disruption of normal bone homeostasis that eventually fuels tumor growth [23].…”
Section: Pathogenesis Of Lung Cancer Metastasis To Bonementioning
confidence: 99%
“…In metastatic cancers involving the bone, denosumab has been shown to suppress markers of bone resorption [4042]. Although bone metastatic lesions from lung cancer invasion are mainly osteolytic [24, 43], cases of mixed lesions have been reported which underscores the need for therapeutic strategies that target both osteolytic and osteoblastic components of bone colonization. Many investigators have reported that blocking osteolytic activity is important even when treating osteoblastic lesions [14].…”
Section: Molecular Targets Implicated In Lung Cancer Bone Metastasismentioning
confidence: 99%